Chronic obstructive pulmonary disease and the development of atrial fibrillation. (1st February 2019) - Grymonprez, Maxim; Vakaet, Vincent; Kavousi, Maryam; Stricker, Bruno H.; Ikram, M. Arfan; Heeringa, Jan; Franco, Oscar H.; Brusselle, Guy G.; Lahousse, Lies
Abstract: Background: Chronic obstructive pulmonary disease (COPD) has been associated with atrial fibrillation (AF). More insight into the epidemiology and underlying mechanisms is required to optimize management. Methods: The Rotterdam Study is a large, population-based cohort study with long-term follow-up. Time dependent Cox proportional hazard models were constructed to study the effect of COPD on incident AF, adjusted for age, sex and pack years of cigarette smoking, and additionally stratified according to exacerbation frequency, left atrial size and baseline systemic inflammatory levels. Results: 1369 of 10, 943 subjects had COPD, of whom 804 developed AF. The AF incidence rate was 14 per 1000 person years in COPD and 8 per 1000 person years in subjects without COPD. The adjusted hazard ratio (HR) for COPD subjects to develop AF as compared to subjects without COPD was 1.28 (95%CI [1.04, 1.57]). COPD subjects with frequent exacerbations had a twofold increased AF risk (HR 1.99 [1.42, 2.79]) and COPD subjects with a left atrial size ≥40 mm also had an elevated AF risk (HR 1.77 [1.07, 2.94]). COPD subjects with baseline systemic inflammatory levels above the median had significantly increased AF risks (hsCRP≥1.83 mg/L: HR 1.51 [1.13, 2.03] and IL6 ≥ 1.91 ng/L: HR 2.49 [1.18, 5.28]), whereas COPD subjects below the median had in both analyses no significantly increased AF risk. Conclusions: COPD subjects had a 28% increased AF risk, which further increased with frequent exacerbations and an enlarged left atrium. The risk was driven by COPD subjects having elevated systemic inflammatory levels. Highlights: COPD is associated with a 28% increased risk of developing atrial fibrillation. Having frequent COPD exacerbations increases the atrial fibrillation risk twofold. COPD subjects with an enlarged left atrium are at higher risk of atrial fibrillation. Systemic inflammation in COPD seems to drive the risk of incident atrial fibrillation.